Review of coronavirus in rats: a potential zoonotic threat - Saulol Hamid Nur-Fazila,; Abd Rahaman Yasmin,; Farzee Faranieyza-Afiqah,; Abdul Rahman Nawal-Amani,; Siti Suri Arshad,; Norfitriah Mohamed Sohaimi, (Universiti Kebangsaan Malaysia, 2023)
The current COVID-19 pandemic has highlighted the importance of the Coronaviridae family as a threat to public health in the emergence of a deadly zoonotic disease. Rats are the possible primary host of the infection as they are highly populated in urban areas, creating a significant epidemic risk. The tendency of coronaviruses (CoVs) to overcome species barriers and adapt to hosts typically found close to humans emphasised the need for further study on coronavirus infection. Sialodacryoadenitis virus (SDAV) and Parker’s rat coronavirus (PRC) are the most commonly isolated pathogens for coronavirus infections in the laboratory and wild rats. They are contagious and could be transmitted to susceptible rats by direct contact, fomites, or aerosol. Coronavirus genera include Alphacoronavirus and Betacoronavirus, which are restricted to bats and other mammalian hosts, while the Gammacoronavirus and Deltacoronavirus are restricted to birds. All known rat coronaviruses are members of the beta genus. Betacoronavirus are divided into five subgenera, i.e., Embecovirus, Hibecovirus, Merbecovirus, Nobecovirus, and Sarbecovirus. All rat coronaviruses are categorised as the Embecovirus subgenus. Most studies have proven that rat coronaviruses are responsible for hepatitis, enteritis, reproductive problems, and respiratory and salivary gland infections, including episcleritis, and dacryoadenitis. The scant literature data, mostly comprising publications from the last century, does not adequately explain the etiopathology of SDAV and PRC infections. This review provides an overview of the knowledge on the characteristics, transmission, clinical signs, pathology, and diagnosis of rat coronaviruses, besides better understanding their zoonotic potentials.